Solid Pseudopapillary Epithelial Neoplasm of the Pancreas: A Rare Entity with Diagnostic Dilemma - Gandhe, Sucheta; Patil, Rahul; Yasam, Venkata Ramesh; Nagarkar, Raj (Annals of the National Academy of Medical Sciences (India), 2023)
The solid pseudopapillary epithelial neoplasm (SPEN) of the pancreas is a relatively uncommon entity. The aim of the present study was to summarize our experiences with regard to diagnostic dilemma, surgery, postoperative follow-up, and management. This retrospective data were collected during the period from January 1, 2018 to December 31, 2020. A total of four patients (three females and one male) were identified within an age range of 13 to 25 years. All the patients were presented with nonspecific symptoms such as abdomen lumps, swelling in the abdomen, and abdominal pain. To reach a definite diagnosis, imaging studies were conducted along with endoscopic ultrasound fine-needle aspiration (EUS-FNA) and biopsy. After confirmation of SPEN on biopsy, all the patients underwent surgery without any complications. Patients are on follow-up, and to date, no metastasis has been detected. SPEN is a rare pancreatic tumor with unusual pathological features leading to a diagnostic dilemma. The pathologist should be familiar with SPEN and its salient histological characteristics that differentiate it from other look-alike pancreatic tumors and can help in timely surgery and management.
Keywords: pancreas; solid pseudopapillary epithelial neoplasm; diagnostic dilemma; immunohistochemistry; surgery